Lemur's guide to healthy eating - Edwards, Lisa; Edwards, Lisa; Lawston, Rachel; Peutrill, Sarah; Roberts, Sian (London Franklin Watts, 2022)
Lemur loves to eat lots of different foods with the rest of his troop. This book follows the story of Lemur and provides lots of advice on healthy eating for its human readers. Topics include eating together, the importance of breakfast, how to eat a balanced diet and snacks and sugary foods. The Healthy Habits series for children aged 4 plus, features key information about how to stay healthy in mind and body, simply told and brought to life through a relatable animal guide alongside bright and gently humorous illustrations. The books have lots of good advice for human children and a little bit of learning about the animal world, to keep things interesting for young animal lovers
Science
Keywords: science